2018
DOI: 10.1002/ar.23842
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vascular Endothelial Growth Factor (VEGF) and Its Family Member Expression After Peripheral Nerve Regeneration and Denervation

Abstract: Vascular endothelial growth factor (VEGF) represents one of the main factors involved not only in angiogenesis and vasculogenesis but also in neuritogenesis. VEGF plays its function acting via different receptors: VEGF receptor1 (VEGFR-1), VEGF receptor2 (VEGFR-2), VEGF receptor3 (VEGFR-3), and co-receptors Neuropilin-1 (NRP1) and Neuropilin-2 (NRP2). This study reports on the first in vivo analysis of the expression of VEGF and VEGF family molecules in peripheral nerve degeneration and regeneration: for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Furthermore, peripheral nerve lesions to the upper limb show a higher prevalence than those to the lower limb in the clinic (Kouyoumdjian et al 2017). Therefore, the rat median nerve injury and repair model is considered to be appropriate for extrapolation toward human upper limb or digital nerve injuries (Jager et al 2014;Muratori et al 2018;Ronchi et al 2018;Dietzmeyer et al 2019). With regard to ethical concerns, this model also represents with the advantage that lesion only partially impairs the upper limb function, because sensitivity and specific motor functions are preserved through innervation by the ulnar and the radial nerve (Bertelli et al 1995;Sinis et al 2006;Jager et al 2014).…”
Section: The Rat Median Nerve Modelmentioning
confidence: 99%
“…Furthermore, peripheral nerve lesions to the upper limb show a higher prevalence than those to the lower limb in the clinic (Kouyoumdjian et al 2017). Therefore, the rat median nerve injury and repair model is considered to be appropriate for extrapolation toward human upper limb or digital nerve injuries (Jager et al 2014;Muratori et al 2018;Ronchi et al 2018;Dietzmeyer et al 2019). With regard to ethical concerns, this model also represents with the advantage that lesion only partially impairs the upper limb function, because sensitivity and specific motor functions are preserved through innervation by the ulnar and the radial nerve (Bertelli et al 1995;Sinis et al 2006;Jager et al 2014).…”
Section: The Rat Median Nerve Modelmentioning
confidence: 99%
“…82,83 There are five members in VEGF family including VEFG-A, VEFG-B, VEFG-C, VEFG-D, and placenta growth factor (PLGF). 84 Among them, VEGF-A participates in the process of wound healing, its transcription and secretion will be elevated and reach the peak at the approximately 7th day after injury. And it mainly influences the proliferative phase.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) on the other hand is a potent angiogenic factor, which promotes proliferation of endothelial cells, formation and permeability of vascular structures [ 35 ]. Nevertheless, several studies demonstrated VEGF for having neurotrophic activities that were mediated either by flk-1 and flt-1 receptor binding or by enhanced vascularization [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%